THE ROLE OF COMMUNICATION IN TOURISM MARKETING - Yulista, Yera (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
Tourism is one of the most developed sectors in Indonesia. The development of the tourism sector is certainly inseparable from the potential possessed by Indonesia, namely the vast archipelago from Sabang to Marauke so that it can support destinations in various regions, plus the diversity of cultures, customs, and regional potentials that open opportunities for access to introduce tourism. Tourism in Indonesia has become a nation's asset, as a driving force for the nation's economy. Indonesian citizens themselves are not a few who are involved in the activities of the world of tourism, both those who act as producers in this case are tourism managers or who choose to become tourists (tourism consumers). Especially for tourism activists, they can make tourism their business way to generate profits by opening a number of tourism facilities, including restaurants, lodging, culinary, souvenirs that symbolize the characteristics of the area and other facilities that support tourism itself. In order to achieve this goal, what must be done is to manage the tourism business optimally, which is then continued by marketing the business so that this tourist spot will be visited by both local and international tourists. This marketing method cannot be separated from the vital role of business communication. Business communication is the main concept in the existence of a tourism business because every party in the business circle will always be connected with various parties with various interests in order to build and maintain the tourism business itself, both managing relationships with internal and external parties. The study of business communication is very complex. In writing this article, the author will focus on building relationships with external parties, namely consumers or more popularly known as tourists/tourists through business communication activities.